2010
DOI: 10.1080/19440041003671262
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the dietary habits and polycyclic aromatic hydrocarbon exposure in primary school children

Abstract: Thirty Italian children, 7-9 year aged, living in Naples were investigated on their dietary habits and on polycyclic aromatic hydrocarbon (PAH) exposure by a food diary-questionnaire and one week duplicate diet sample analyses. \ud Daily total food consumption mean value was 632±215 g day-1, median value 613 g day-1. The daily energy intake and the diet composition meanly agreed with the official guidelines for the Italian children.\ud 16 PAHs were simultaneously detected and, according to the EFSA approach, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Although PAHs are present in meat and meat products, they are usually not considered as a specific causal agent for the carcinogenic activity of red and processed red meat products as they are present in all foods (Cirillo et al, 2010). Indeed, comparable levels of PAHs are found in cereal products and in grilled poultry and fish, foods not found to be associated with an increased risk for CRC.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Although PAHs are present in meat and meat products, they are usually not considered as a specific causal agent for the carcinogenic activity of red and processed red meat products as they are present in all foods (Cirillo et al, 2010). Indeed, comparable levels of PAHs are found in cereal products and in grilled poultry and fish, foods not found to be associated with an increased risk for CRC.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Cirillo et al. (2010) reported that the daily median exposure values of BaP, PAH4, and PAH8 in primary school children were 5, 28, and 54 ng/kg bw/day, respectively. Rozentale et al.…”
Section: Resultsmentioning
confidence: 99%
“…Cirillo et al investigated the dietary habits of children of Naples through a food diary questionnaire. A 1‐week duplicate diet method, comparing PAH results about dairy products with our ‘mozzarella cheese’ data, found B(g,h,i)PE and DB(a,h)A median levels lower than our results and a CHR median quite similar to that obtained by Cirillo.…”
Section: Resultsmentioning
confidence: 99%
“…The highest concentration of PAHs is produced at the end of the smoking processes, then it decreases due to light decomposition and interaction with other compounds. Therefore the smoke can be a significant source of PAH contamination of food representing a problem for the consumer safety …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation